Assessment of The Impact Covid-19 on The Environment and Water Resources: A Namibian Perspective - Nwagbara, Victor Uzoma; Iikela, Sioni; Iyama, William Azuka (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2024)
The widespread spread of Covid-19 globally has hampered many socio-economic activities and caused many negative impacts on the environment and water resources. Industrial activity came to a halt and this brought the global economy to a halt while water demand and consumption skyrocketed as the UN urged people to wash their hands to fight the COVID19 pandemic. Namibia is no exception in terms of the negative impact of COVID19 on the environment and water resources as it is considered one of the driest countries in Sub-Saharan Africa. This research method uses a persuasive-based qualitative description approach. To facilitate understanding and reading, the research results are described first. The results in the field are that In Namibia, more than 20% of the population, especially those living in rural areas, do not have access to good quality water and do not have a safe sanitation system. The continuation and extension of the nationwide lockdown deepens the recession and indirectly impacts the environment and water bodies.